(untitled) (Communication & Society, 2023)
This paper explores editorials and opinion columns published in four Chilean mainstream newspapers and analyzes how China is represented within the context of Chinese economic advances in the region and the contextual narratives surrounding bilateral relations. Through a content analysis of editorials and opinion pieces of elite media between 2018 and 2021, this study allows an understanding of how China and its growing influence are perceived locally. Ultimately, despite an overall alignment with China’s public diplomacy centered around an economic-commercial dimension, there are still nuances in how China is represented in Chilean op-eds.